PENGARUH TEKNIK COGNITIVE RESTRUCTURING UNTUK MENINGKATKAN SELF ESTEEM SISWA MELALUI BIMBINGAN KELOMPOK DI SMP NEGERI 21 PEKANBARU - Efi Susanti; Rosmawati Rosmawati; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: This study aims to determine the differences in student self esteem before and after Cognitive Restructuring technique was applied through group guidance and to determine the effect of Cognitive Restructuring techniques to improve student self esteem through group guidance. The study was conducted at Pekanbaru State 21 Middle School against 7 subjects with a purposive sampling technique. The research design was pre-experiment with the one group pre-test post-test model. The instrument of data collection used is the scale of self-esteem measurement. The results showed that there were differences in self-esteem of students before and after being given the Cognitive Restructuring technique with a significance value of 0.018 <0.05. In addition, based on the Spearman rank test, it is known that there is a significant influence between Cognitive Restructuring techniques to improve students' self esteem with a significance value of 0.033 <0.05. The effect of Cognitive Restructuring techniques to improve student self esteem is 63% while 37% is influenced by other factors that come from within and from the student's environment. From the results obtained, it is recommended that educational institutions should continue to carry out activities that are able to improve student self esteem in the teaching and learning process to encourage more positive self-development, physical, social, family, and moral-ethics.Key Words : Cognitive Restructuring Technique, Self Esteem,, Group Guidance